Opportunities and Challenges for Field Experiment Equipment - Sh. Shang; J. Wang (Сельскохозяйственные машины и технологии)
Modern seed industry development could contribute up to 40 percent to increase agricultural production and effi ciency. Mechanization of fi eld experiments is an important means to improve the effi ciency and precision of fi eld breeding experiments. There is a big gap in the mechanization level and development of fi eld experiments in diff erent countries of the world. The International Association on Mechanization of Field Experiments established in 1964 has played a great role in promoting the development of fi eld experiment mechanization in the world. At present, the advanced fi eld experiment equipment is mainly concentrated in international manufacturers such as Wintersteiger in Austria, Almaco in the United States, Haldrup and Zürn in Germany. As a great agricultural country, China’s demand for rice and maize seeds, the major food crops in the last 10 years, is about 250 million kilograms and 1.15 billion kilograms, respectively. A large amount of demand for seeds prompted China’s fi eld experiment mechanization that has made great progress. The research team of Qingdao Agricultural University has developed 16 types of new plot planters and plot harvesters which have been popularized and applied in China. But diff erent crops, planting patterns and regional characteristics put forward higher requirements for adaptability of fi eld experiment equipment. The precision of the seeder, the cleaning performance of the seeding and harvesting equipment and the intelligent technology of the equipment need to be further improved. In future development, more attention should be paid to the integration of modern information technology and intelligent technology into fi eld test equipment, to improve operational effi ciency and accuracy.